(untitled) (Revista Archai, 2024)
In ancient times, authors such as Plutarch and Proclus questioned Parmenides’ abilities as a poet considering his Poem to be ‘prose in disguise’. Harsh judgments concerning Parmenides’ style are pervasive even in modern scholarship (Diels, 1897; Wilamowitz, 1912; Tarán, 1977; Kirk & Raven, 1977). This paper focuses on specific metrical and rhythmic devices used consistently in the composition of the Poem, that I will refer to, collectively, as ‘poetic dislocation’. This term encompasses the blurring and cancellation of the central caesura, the tendency to break Hermann’s bridge with varying degrees of intensity, the accumulation of enjambment in groups of verses, the use of non-traditional lexicon of the epic genre and the placement of Homeric lexicon in non-Homeric hexameter collocations. My attempt is to prove that these procedures are an integral part of Parmenides’ poetic style. I will also present an analysis of Parmenides’ versification focusing on the rhythmic patterns and the organization of caesura, especially in fr. B8.